MANAGERIAL ECONOMICS: UNDERSTANDING ECONOMIC OPTIMIZATION - Joko Hadi Purnomo (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Abstract, Changes in the business environment will occur at any time, generally in theform of changes in one or a combination of environmental factors outside thecompany, both on a national, regional and global scale. Business uncertainty willusually increase when the economic cycle is down, for example when we enter themillennium century, and then become optimistic when the economic cycle increases.The performance of a company will be greatly influenced by government policies inthe economic, monetary, fiscal, trade and investment sectors. Economic developmentin developing countries such as Indonesia is also influenced by the sharpness of thevision, mission and development strategies carried out by the government regime. Inmonitoring the economic turmoil because these factors can directly affect therealization of the achievement of business plan targets, the quality of businessprocesses and the achievement of company performance benchmarks in a sustainablemanner. The inflation rate is the most important economic variable that directlyaffects the condition of consumer purchasing power and the company's productioncost structure. Meanwhile, the development of interest rates should always bemonitored by the company, considering that this main economic variable is the basisor barometer for activities that are feasible or not appropriate for a business to run.Management decisions in today's business world are no longer solely based oneconomic considerations. According to the principles of economics, which were laterrevealed to the branch of managerial economics, management decisions lead to thegoal of maximizing profits, especially economic profits. Developments show thatbusiness decisions have psychological influences on decision makers, as well as socialinfluences where business entities and decision makers interact with the environment.Keywords: managerial economics, economic optimization, Indonesia.